Principles and Practices of Dowry in Law Islamic Marriage: Between Tradition and Modernity - Siti Hadijah; Riza Aulia; Ilham Maulana; Prawira Putra Amanda (ISNU Sumatera Utara, 2025)
This study examines the dynamics of dowry in Islamic marriage law, considering both traditional and modern aspects that influence its practice in contemporary society. Dowry, as a mandatory gift from a prospective husband to his prospective wife, has undergone various interpretations and adaptations over time. This study analyzes the legal basis of dowry in Islamic law, including the provisions of the Quran, Hadith, and the opinions of scholars, and explores how dowry practices have evolved in different socio-cultural contexts. The discussion covers the various forms of dowry, from traditional property to modern assets, and their implications for women's rights and gender equality in Islamic marriage. The results demonstrate flexibility in determining dowry, allowing for adaptation to contemporary socio-economic conditions while maintaining its spiritual essence as a symbol of commitment and respect for women. This study also identifies challenges in balancing traditional values with the demands of modernity and provides recommendations for harmonizing dowry practices in accordance with Sharia principles and the contemporary context.